Cashew Nut Shell Liquid (Anacardium occidentale) as a Botanical Insecticide to Control Helopeltis sp on Cocoa plants - Santi, Idum Satia; Kurniawan, Indra; Manto, Agus (Tropical Plantation Journal, 2024)
Cashew nut skin is considered as waste, whereas cashew nutshell extract, or called CNSL (Cashew Nut Shell Liquid), has the potential as a botanical insecticide that can control insect pests. Helopeltis sp is a pest that often attacks cacao plants. The study aims to determine the effectiveness of cashew nutshell extract as a botanical insecticide to control  Helopeltis sp. in cacao plants. The study used a randomized block design (RBD) with seven treatments and three replications. Testing CNSL on adult (imago) and pre-adult (nymph) insects. CNSL concentrations used are 0%, 3.125%, 6.25%, 12.5%, 25%, 50% and 100%. The results showed that cashew nutshell extract has strong toxicity. A concentration of 3.125% can kill 100% of the imago Helopeltis sp. (72 hours after application) for the nymph Helopeltis sp. (48 hours after application). LC50 values 24 hours after application for imago and nymph were 4.63% and 0.94%, and LC99 for imago and nymph was 42.62% and 23.89%.  Furthermore,  cashew nut extract can be used as a botanical insecticide to control other plant pests.